The Applicability of the Lamendin Method to Skeletal Remains Buried for a 16‐Year Period: A Cautionary Note. (20th November 2014) - De Angelis, Danilo; Mele, Elia; Gibelli, Daniele; Merelli, Vera; Spagnoli, Laura; Cattaneo, Cristina
Abstract: The Lamendin method is widely reported as one of the most reliable means of age estimation of skeletal remains, but very little is known concerning the influence of burial in soil. This study aimed at verifying the reliability of the Lamendin method on corpses buried for 16 years in a cemetery. The Lamendin and the Prince and Ubelaker methods were applied. In all age groups except the 40‐ to 49‐year–olds, the error was higher in the buried sample. The age‐at‐death error ranged between 10.7 and 36.8 years for the Lamendin method (vs. the reported 7.3–18.9 years) and 9.5 and 35.7 for the Prince and Ubelaker one (vs. the original 5.2–32.6 years); in all age groups, the error is closer to that found on archeological populations. These results suggest caution in applying the Lamendin method to forensic cases of human remains buried even for a brief period under soil.